The Influence of Principals’ Adaptive Leadership And The School Psychological Environment On Teacher Creativity In Instructional Implementation At Muhammadiyah Junior High School Manado - Kartin Jhony; Joulanda Rawis; Roos Maria Stela Tuerah (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the influence of principals’ adaptive leadership and the school psychological environment on teacher creativity in instructional implementation at Muhammadiyah Junior High School Manado. The research employed a quantitative approach using a survey method involving the entire teacher population of 35 individuals through a saturated sampling technique. Data were collected using structured questionnaires and analyzed through multiple linear regression. The results indicate a strong relationship among the variables, with a correlation coefficient (R) of 0.768 and a coefficient of determination (R Square) of 0.590, meaning that 59% of the variation in teacher creativity can be explained by adaptive leadership and the psychological environment. Partially, adaptive leadership has a significant effect (t = 3.219), as does the school psychological environment (t = 3.607), which demonstrates a relatively greater contribution. Simultaneously, both variables significantly influence teacher creativity, with an F-value of 23.187. In conclusion, flexible school leadership and a supportive work atmosphere are crucial factors in fostering teacher innovation in designing and implementing the learning process.